Kajian Retorika Visual Iklan dalam Kampanye BCA “Don’t Know? Kasih No!” (Versi Audio Visual) - Gozali, Jessica; Mansoor, Alvanov Zpalanzani; Satria, Firmanda (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2025)
Increased cybercrime in modern era has prompted Bank Central Asia (BCA), the largest private bank in Indonesia, to release an audio-visual advertisement for the “Don't Know? Kasih No!” Campaign to educate people regarding the dangers and modes of phishing crimes on December 8, 2023, on BCA's YouTube. The ad received lots of positive responses and reached 45 million views within two months, proving its quality. This descriptive qualitative study analyzes the ad's visual rhetorical messages through scene screenshots. This research uses visual rhetoric theory by Sonja K. Foss and content analysis methods to study the advertisement, with the steps of taking screenshots of scenes then analyzing the audio, angles, shots, and figures of speech of those scenes. The results of the analysis show that the majority used in the scenes are metaphors, eye level angles, and close-up shots to convey an interesting and effective message, engage the audience, and emphasize the message about the importance of being cautious of unclear sources links and rethink before giving out personal identification. The use of strong visual rhetoric in the advertisement has the potential to increase public awareness and understanding of phishing. The findings of this research have significant implications for advertising practitioners, mass media, and researchers. Advertising practitioners can use these findings to develop more effective educational advertising using visual rhetoric. Mass media can use these findings to increase public awareness about phishing. Researchers can use these findings in future research to develop a more comprehensive use of visual rhetoric.